2019
DOI: 10.1111/jfpe.13065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ball milling time on physicochemical properties of Cordyceps militaris ultrafine particles

Abstract: Cordyceps militaris powder with different particle sizes, a fungus rich in cordycepin and carotenoids, has different physicochemical properties. To explore the influence of different ball milling time on the properties, a batch ball‐mill was used before high energy nano‐impact mill to produce ultrafine particles from Cordyceps militaris. The particle formation kinetics was covering 2 to 16 hr of grinding was measured and explained. The surface charge (zeta potential), surface activity (surface tension), polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Ample studies have reported that micronization of carotenoids results in their increased bioavailability [110,111]. Generally, carotenoid micronization is conducted by milling, grinding, and chemical precipitation [112,113,114]. However, there are some concerns regarding the above conventional methods, as carotenoids are easily decomposed by friction heat and oxygen contact.…”
Section: Improvement Of Carotenoid Processing Efficiency By Z-isommentioning
confidence: 99%
“…Ample studies have reported that micronization of carotenoids results in their increased bioavailability [110,111]. Generally, carotenoid micronization is conducted by milling, grinding, and chemical precipitation [112,113,114]. However, there are some concerns regarding the above conventional methods, as carotenoids are easily decomposed by friction heat and oxygen contact.…”
Section: Improvement Of Carotenoid Processing Efficiency By Z-isommentioning
confidence: 99%
“…Superfine grinding is a potential technique for the production of various superfine powders. Research on superfine grinding has already been advanced using various materials, such as green tea, 9 asparagus pomace, 10 horseradish, 11 Cordyceps militaris , 12 and sugar beet pulp powders 13 . Previous studies have revealed that superfine grinding technology endows food materials with special characteristics in comparison with coarse particles, including higher bioactive substance content, stronger antioxidant capacity, better solubility and absorbability, and enhanced surface properties 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…Freeze‐drying is not widely used in MR drying due to its high energy consumption. To save energy, the by‐products can be crushed to accelerate the drying process 48,49 . The crushed fine powder form is also more convenient for food formulations.…”
Section: Mushroom By‐productsmentioning
confidence: 99%
“…To save energy, the by-products can be crushed to accelerate the drying process. 48,49 The crushed fine powder form is also more convenient for food formulations. Mushroom residue crushing methods can be divided into mechanical methods, chemical methods, and enzyme methods.…”
Section: Mushroom Residuementioning
confidence: 99%